Overlooked places and peoples
1 online resource.
Keywords: "This book examines the hemispheric histories of overlooked peoples and places that shaped colonial Spanish America. This volume focuses on the experiences of Native peoples, Africans and Afro-descended peoples, and castas (individuals of mixed ancestry) living in regions perceived as fringe, marginal, or peripheral. It covers a comprehensive geographic range including northern Mexico, Central America, the Circum-Caribbean, and South America, as well as a sweeping chronological period, from the earliest colonization episodes of the sixteenth century to the twilight of Spanish rule in the late eighteenth century. The chapters highlight the diverse peoples, from semisedentary and nonsedentary Native groups and Mosquito captains to free African governors-who lived, labored, fought, ruled, and formed communities across Spanish America. The volume examines how these overlooked peoples navigated colonial processes of conquest, displacement, and relocation, while drawing attention to local factors that influenced these experiences including ecological change, rivalries, diplomacy, contraband, time and distance, and geography. Through their analysis of the local and temporal contexts, the studies in this volume offer new insight into why the protagonists of these places responded contentiously-through resistance or flight-or cooperatively-by accepting treaties or alliances. Non-specialists-undergraduate students, booksellers, and librarians will be drawn to the individuals case studies, while scholars will find this collection to be an indispensable research tool"--